Case report: Thoracoscopic ablation for a patient with atrial fibrillation and persistent left superior vena cava - Liu, Haozhong; Tan, Tong; Qiu, Hailong; Chen, Jimei; Liu, Jian; Wei, Peijian; Guo, Huiming (Frontiers in Cardiovascular Medicine, 2023)
Persistent left superior vena cava (PLSVC) is a relatively rare congenital anomaly in the general population. It plays an important role in initiating and maintaining atrial fibrillation (AF) in some patients. Radiofrequency catheter ablation is the major treatment for patients with AF and PLSVC in most publications. Here, we reported a case of thoracoscopic ablation for a patient with atrial fibrillation and persistent left superior vena cava. After preprocedural simulation using virtual reality, we successfully completed box-lesion, ablation line from superior vena cava to inferior vena cava, left atrial appendage (LAA) excision, and PLSVC ablation. It provides a new perspective on surgical treatment for patients with AF and PLSVC.